Therapeutic treatment in the elderly with heart failure - Martyna Lamtych; Karolina Kubiak; Hanna Bednarek; Pamela Świerczek; Karolina Cięszka; Daria Bieniek; Filip Biernacki; Zuzanna Leśniak; Natalia Skierkowska; Marta Cybulska; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Heart failure (HF) is a clinical syndrome that is the last common stage in many cardiovascular diseases. The main causes leading to the development of HF are, among others, primary impairment of myocardial contractility, volume and / or ventricular congestion, and obstruction of the diastolic duct due to pericardial diseases. The methods of detecting heart failure include: an accurate interview with the patient, laboratory tests and echocardiography. Treatment options include non-pharmacological, pharmacological and surgical treatment. A very important aspect of cure is also physical activity and appropriate nutritional treatment.